The salience of Black mentors on the teaching praxis of Latino male teachers. Issue 3 (3rd May 2020) - Hayes, Cleveland
ABSTRACT: Despite the growing population of Latino students, little has been done to recognize the potential cultural assets and resilience that Latino communities and Latino teachers can bring to the educational environment. Using Critical Race Theory, in this article, each participant shares their experiences with their Black mentors. This article shares the ways in which Black teachers continue to exemplify Black teaching excellence now with a group that isn't Black.